Prevalence and associated factors of overweight and obesity among medical students from the Western Balkans (South-East Europe Region) - Ilić, Miloš; Pang, Huiwen; Vlaški, Tomislav; Grujičić, Maja; Novaković, Budimka (BMC public health, 2024)
Being overweight and obese is associated with an elevated risk of developing noncommunicable diseases, which are the leading causes of mortality worldwide. It is a warning that global prevalence of overweight among university students ranges from 20 to 40%, which presents a significant public health problem. To date, there was no research conducted on medical students regarding the prevalence and associated factors of overweight and obesity in the countries of the Western Balkans (Slovenia, Croatia, Bosnia and Herzegovina, North Macedonia, and Serbia). The aim of this study was to determine the prevalence and potential demographic, socioeconomic, and health-related behavioral factors associated with overweight and obesity of medical students from Western Balkans. A cross-sectional study was conducted, surveying 2452 students from 14 medical faculties from 5 countries in the region. The prevalence of overweight was 12% and obesity was 2.3% among medical students from Western Balkans. Male gender and smoking status are significant positive predictors of overweight and obesity. Daily level of physical activity up to 1 h per day, going to preventive check-ups once a year or as a part of annual dormitory check-ups are associated with lower odds of being overweight and obese. By creating adequate public health educational programs, students can be influenced to acquire proper health-related lifestyle habits, which would lead to reducing the prevalence of overweight and obesity among the student population, as well as risk of developing noncommunicable diseases and improving the overall health of the population.